2014
DOI: 10.1017/s0950268814001083
|View full text |Cite|
|
Sign up to set email alerts
|

A windy day in a sheep saleyard: an outbreak of Q fever in rural South Australia

Abstract: In December 2004, the Department of Human Services investigated an outbreak of Q fever in South Australia. A case-control study tested an association between attending a local saleyard and human illness. A case was defined as a person with clinical illness and evidence of seroconversion or high phase II IgM. Controls were selected from a database of community controls matched on sex, age group and postcode. Matched analysis of the first 15 cases with 45 controls indicated that contracting Q fever was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Since our sampling was mainly performed in rural areas, poor hygiene could exacerbate the spread of Coxiella burnetii (Luoto 1960;Lyytikäinen et al 1998). It appears that the camel is likely to harbor high levels of Coxiella burnetii and capable of shedding the bacterium through milk, blood, feces, and urine and especially in birth by-products (Arricau-Bouvery and Rodolakis 2005;TissotDupont et al 2007;Schimmer et al 2010;Bielawska-Drózd et al 2013;Tozer et al 2013;Mohammed et al 2014;Schimmer et al 2014;O'Connor et al 2015;Pimenta et al 2015;Moffatt et al 2015;Nusinovici et al 2015;van den Brom et al 2015). Environment contamination of Coxiella burnetii events lasts for months and even years; so, inhalation of dust (aerosol contamination) is also very critical for farm animals and public health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since our sampling was mainly performed in rural areas, poor hygiene could exacerbate the spread of Coxiella burnetii (Luoto 1960;Lyytikäinen et al 1998). It appears that the camel is likely to harbor high levels of Coxiella burnetii and capable of shedding the bacterium through milk, blood, feces, and urine and especially in birth by-products (Arricau-Bouvery and Rodolakis 2005;TissotDupont et al 2007;Schimmer et al 2010;Bielawska-Drózd et al 2013;Tozer et al 2013;Mohammed et al 2014;Schimmer et al 2014;O'Connor et al 2015;Pimenta et al 2015;Moffatt et al 2015;Nusinovici et al 2015;van den Brom et al 2015). Environment contamination of Coxiella burnetii events lasts for months and even years; so, inhalation of dust (aerosol contamination) is also very critical for farm animals and public health.…”
Section: Discussionmentioning
confidence: 99%
“…Many other authors previously have reported antibodies against Coxiella burnetii in the sera of camels (Mathur and Bhargava 1979), with no clinical sign. It is generally known that farm animals serve primarily as asymptomatic carriers of Coxiella burnetii and that organism resides abundantly in their placenta and udder and may be shed for extended periods in milk, urine, feces, and birth fluids thus exposing other animals, and people to Coxiella burnetii (Maurin and Raoult 1999;Tissot-Dupont et al 2007;Tozer et al 2013;O'Connor et al 2015;Pimenta et al 2015). Therefore, owing to camel booming potential for meat/milk production, biomedicine, and agrotourism in this harshly dried environment (i.e., the agroecologically and geopolitically important current study zone), ordinary people are simply contacted by camel, and camel contribution to the risk of Q fever in human should be established without reasonable doubt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of research in Australia tends to focus on analysis of notified cases (35), unusual outbreaks, (36, 37), or animal and environmental sources (38). However, a recent study by Bond et al (39) demonstrated the application and outcomes of taking a One Health approach to an outbreak associated with a goat farm.…”
Section: Resultsmentioning
confidence: 99%